Effects of Acute Exercise and Training on the Sarcoplasmic Reticulum Ca2+ Release and Uptake Rates in Highly Trained Endurance Athletes - Gejl, Kasper Degn; Andersson, Erik P.; Nielsen, Joachim; Holmberg, Hans-Christer; Ørtenblad, Niels (Frontiers in Physiology, 2020)
Little is presently known about the effects of acute high-intensity exercise or training on release and uptake of Ca2+ by the sarcoplasmic reticulum (SR). The aims here were to characterize this regulation in highly trained athletes following 1) repeated bouts of high-intensity exercise and 2) a period of endurance training including high-intensity sessions. Eleven cross-country skiers (25±4yrs, 65±4 mL O2·kg-1·min-1) performed four self-paced sprint time-trials (STT 1-4) lasting ≈ 4 min each (STT 1-4) and separated by 45 min of recovery; while 19 triathletes and road cyclists (25±4yrs, 65±5 mL O2·kg-1·min-1) completed 4 weeks of endurance training in combination with three sessions of high-intensity interval cycling per week. Release (µmol·g-1 prot·min-1) and uptake (tau (s)) of Ca2+ by SR vesicles isolated from m. triceps brachii and m. vastus lateralis were determined before and after STT 1 and 4 in the skiers and in m. vastus lateralis before and after the 4 weeks of training in the endurance athletes. The Ca2+ release rate was reduced by 17-18% in both limbs already after STT 1 (arms: 2.52±0.74 to 2.08±0.60; legs: 2.41±0.45 to 1.98±0.51, P < 0.0001) and attenuated further following STT 4 (arms: 2.24 ± 0.67 to 1.95 ± 0.45; legs: 2.13 ± 0.51 to 1.83 ± 0.36, P < 0.0001). Also, there was a tendency towards an impairment in the SR Ca2+ uptake from pre STT1 to post STT4 in both arms and legs (arms: from 22.0 ± 3.7s to 25.3 ± 6.0s; legs: from 22.5 ± 4.7s to 25.5 ± 7.7s, P = 0.05). Endurance training combined with high-intensity exercise increased the Ca2+ release rate by 9% (1.76±0.38 to 1.91±0.44, P = 0.009), without altering the Ca2+ uptake (29.6±7.0 to 29.1±8.7 s; P = 0.98). In conclusion, the Ca2+ release and uptake rates by SR in exercising limbs of highly trained athletes declines gradually by repetitive bouts of high-intensity exercise. We also demonstrate, for the first time, that the SR Ca2+ release rate can be enhanced by a specific program of training in highly trained athletes, which may have important implications for performance parameters.